1998
DOI: 10.1046/j.1469-7580.1998.19220195.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic endocrine cells in Bufo bufo: immunocytochemistry and ultrastructure

Abstract: The endocrine pancreas of the toad consists of rounded islets of various sizes embedded in the exocrine tissue. Isolated cells are also present. At least 4 types of endocrine cell are distinguishable by shape, size and electrondensity of the secretory granules as well as by their immunoreactivity with different antisera : insulin, somatostatin, pancreatic polypeptide, and glucagon cells. Insulin cells can be divided into 2 types according to their cytoplasmic electrondensity. Colocalisation of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…5 b). Four types of endocrine cells were identified in a previous work (Accordi et al 1998), according to their immunoreaction with different antisera : insulin, glucagon, somatostatin and pancreatic polypeptide cells. Our observations showed that the structure of pancreatic cells remained unaffected during pre-and prometamorphosis, until the beginning of metamorphic climax, characterised by the emergence of fore limbs and by tail resorption.…”
Section: Electron Microscopymentioning
confidence: 99%
“…5 b). Four types of endocrine cells were identified in a previous work (Accordi et al 1998), according to their immunoreaction with different antisera : insulin, glucagon, somatostatin and pancreatic polypeptide cells. Our observations showed that the structure of pancreatic cells remained unaffected during pre-and prometamorphosis, until the beginning of metamorphic climax, characterised by the emergence of fore limbs and by tail resorption.…”
Section: Electron Microscopymentioning
confidence: 99%
“…3b). Four types of endocrine cells were identified in a previous work (Accordi et al. 1998), according to their immunoreaction with different antisera: Insulin, Glucagon, Somatostatin and Pancreatic Polypeptide cells.…”
Section: Resultsmentioning
confidence: 99%
“…This may reflect evolutionary adaptations to different diets or other environmental conditions (Cabrera et al, ). Ultrastructural studies have shown that the number of endocrine cell types differs among vertebrate species (Accordi, Bracci, & Ventola, ; Lozano, Hernandez, & Agulleiro, ; Etayo et al, ). These differences are summarized in Table .…”
Section: Introductionmentioning
confidence: 99%